Implementation and Use of Base64 Algorithm in Video File Security - Efendi, Muhammad; Volvo Sihombing; Parulian, Sahat (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Personal data is often the target of irresponsible people to misuse. The theft is carried out to profit from the person who has the data. In addition to the theft of work files, theft is also carried out on video files. The theft of this file aims to find out what the contents of the video are. Someone has a private video recording that should not be known by others. Misuse of video files will be fatal for the owner of the video. Cryptographic techniques are needed in video security. Caesar Cipher algorithm can help users in securing the video file. The Base64 algorithm can be used to change the ASCII 256 format to Base64 so that it is easy to send or store in a storage media. This algorithm will make the file structure simpler so that it can be displayed and saved. By applying the Base64 algorithm and Caesar Cipher on video files, the security and confidentiality of the files will be guaranteed